The Chinshō Yasha-hō 鎮將夜叉法 and the Adaptation of Tendai Esoteric Ritual - Gosselin, Pei-Ying Lin (Religions, 2023)
This study aims to investigate the ritual of a peculiar scripture entitled Chinshō yasha-hō 鎮將夜叉法 (Ch. Zhenjiang yecha fa. “Tantric Ritual of Chinshō Yakṣa”). The Japanese deity Chinshō Yakṣa is a Tendai variation of Vaiśravaṇa (Ch. Pishamen/Jp. Bishamon 毘沙門), a heavenly king who vowed to protect Buddhism. The ritual of Chinshō Yakṣa is a major ritual in Tendai Esotericism. It has been traditionally accepted that this scripture was transmitted from China. Modern scholarship, however, suspects that this ritual is Saichō’s 最澄 (767–822) invention. This study examines the contents and characters involved in this ritual manual by comparing other ritual manuals of Vaiśravaṇa. In analysing its liturgical aspect, as well as its textual relationship with other ritual manuals, this paper illustrates how the Chinshō yasha-hō deviates from the other ritual manuals and evaluates the possible sources or origins regarding the formation of this ritual. Similar mudrās and mantras that appear in both the Chinshō yasha-hō and other texts were identified, implying that the Chinshō yasha-hō might have drawn from multiple sources. Moreover, judging from its similarity with Chinese Tiantai ritual manuals and other texts that were forged in the Tang dynasty, it is possible that Tang China and Japan saw a period of active ritual invention.